Giant Bilateral Adrenal Myelolipoma with Congenital Adrenal Hyperplasia - S. Al-Bahri; A. Tariq; B. Lowentritt; D. V. Nasrallah (Case Reports in Surgery)
Myelolipomas are rare and benign neoplasms, predominant of the adrenal glands, consisting of adipose and mature hematopoietic tissue, commonly discovered incidentally with increased use of radiologic imaging. Few cases of giant bilateral adrenal masses are reported, especially in the setting of congenital adrenal hyperplasia (CAH). We report the case of a 39-year-old male with a history of CAH secondary to 21-α hydroxylase deficiency on steroids since childhood, self-discontinued during adolescence, presenting with abdominal distension, fatigue, decreased libido, and easy bruising. Imaging revealed giant bilateral adrenal masses. He subsequently underwent bilateral adrenalectomy found to be myelolipomas measuring 30 × 25 × 20 cm on the left and weighing 4.1 kg and 25 × 20 × 13 cm on the right and weighing 2.7 kg. Adrenal myelolipomas are found to coexist with many other conditions such as Cushing’s syndrome, Addison’s disease, and CAH. We discuss the association with high adrenocorticotropic hormone (ACTH) states and review the studies involving ACTH as proponent leading to myelolipomas. Massive growth of these tumors, as in our case, can produce compression and hemorrhagic symptoms. We believe it is possible that self-discontinuation of steroids, in the setting of CAH, may have resulted in the growth of his adrenal masses.